2000
DOI: 10.1115/1.1343457
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Performance for Varying Density Ratio Coolants on an Airfoil With Strong Curvature and Pressure Gradient Effects

Abstract: An experimental study was conducted to investigate the film cooling performance on the suction side of a first-stage turbine vane. Tests were conducted on a nine times scale vane model at density ratios of DR=1.1 and 1.6 over a range of blowing conditions, 0.2⩽M⩽1.5 and 0.05⩽I⩽1.2. Two different mainstream turbulence intensity levels, Tu∞=0.5 and 20 percent, were also investigated. The row of coolant holes studied was located in a position of both strong curvature and strong favorable pressure gradient. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The distributions of η were similar for both DRs, but the DR = 1.8 coolant had a peak film effectiveness ofη = 0.38, whereas for DR = 1.2 the peak was η = 0.32. This may be attributed to better lateral distribution of the high-density coolant as noted by Sinha et al 12 Scaling of film effectiveness performance on simulated turbine airfoils was investigated by Cutbirth and Bogard 13 for the showerhead and pressure side of a vane, and by Ethridge et al 14 for the suction side of a vane. Showerhead cooling for low and high mainstream turbulence levels, T u = 0.5% and 20% respectively, was studied by Cutbirth and Bogard 13 for coolant DR = 1.2 and 1.8.…”
Section: Scaling Of Film-cooling Performance With Varying Drmentioning
confidence: 96%
“…The distributions of η were similar for both DRs, but the DR = 1.8 coolant had a peak film effectiveness ofη = 0.38, whereas for DR = 1.2 the peak was η = 0.32. This may be attributed to better lateral distribution of the high-density coolant as noted by Sinha et al 12 Scaling of film effectiveness performance on simulated turbine airfoils was investigated by Cutbirth and Bogard 13 for the showerhead and pressure side of a vane, and by Ethridge et al 14 for the suction side of a vane. Showerhead cooling for low and high mainstream turbulence levels, T u = 0.5% and 20% respectively, was studied by Cutbirth and Bogard 13 for coolant DR = 1.2 and 1.8.…”
Section: Scaling Of Film-cooling Performance With Varying Drmentioning
confidence: 96%
“…The adiabatic effectiveness was corrected for 1D conduction through the wall using the following equation, after Ethridge et al [10]:…”
Section: Experimental Facilities and Proceduresmentioning
confidence: 99%
“…However, the curvature of the concave surface results in a reattachment of the lifted-off coolant on the pressure side, resulting in higher downstream effectiveness. Ethridge et al (2001) studied the effect of coolant-to-mainstream density ratio on a vane with high curvature. Dittmar et al (2002) studied different film cooling hole configurations on the suction (convex) side and concluded that shaped holes provide better coverage at higher blowing ratios by resisting jet penetration into the mainstream.…”
Section: Blade Surface Film Coolingmentioning
confidence: 99%